Changes in patterns and outcomes of trauma patients after betterment in law and order situation of the city - Saqib , Sabah Uddin; Zafar, Hasnain (Journal of the Pakistan Medical Association, 2021)
Objective: To assess the impact of the law and order situation of a city on the pattern of traumatic injuries and the overall outcomes of trauma victims. Method: The retrospective study of prospective trauma surgery data was done at Aga Khan University Hospital, Karachi, and comprised data of patients with torso injuries before the improvement of law and order situation from January 2012 to March 2013 in Group A, and of those with similar injuries after the law and order situation improved in the city from January 2018 to March 2019 in Group B. The required data was collected by a single researcher using a predesigned questionnaire. Inter-group comparison was done to see the difference in patterns of injuries and outcomes. Data were analysed using SPSS 22. Results: Of the 676 cases reviewed, Group A had 416(61.5%); 363(87%) males and 53(13%) females with overall mean age of 37+/-13 years. Group B had 260(38.5%); 219(84%) males and 41(16%) females with overall mean age of 36+/-13 years (p>0.05). Penetrating trauma alone or combined with blunt force was the most common mechanism in Group A i.e. 245 patients (59%), while in group B blunt trauma was the commonest cause 209 patients (80.4%). There was an overall 37.5% (156 cases) reduction in torso trauma cases. Mortality in Group A was 22(5.3%) and in Group B it was 7(2.7%). Conclusion: With the improvement in the law and order situation, there was reduction in overall trauma cases and the pattern of trauma shifted from penetrating Continuous...